Ethnobotany of Banana Stock on The Normality of Uterial Involution in Lapandewa Village, South Buton Regency - Syastriani Isna Putri Syarif; Wa Ode Nesya Jeni Samrida (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The people of Lapandewa village, South Buton district, are used to doing ethnobotany by using water from the banana stem plant or commonly called the lower banana stem as an alternative in traditional medicine consumed during the puerperium because it is believed to help facilitate the process of uterine involution to minimize the occurrence of preventing bleeding. The purpose of this study was to determine the normality of uterine involution in postpartum mothers who consumed water from banana stems. The method used is Quasi Experiment; the intervention carried out is that postpartum mothers drink water that has been taken from banana stems ±20-30ml and allowed to stand for ±10 minutes to separate fiber or dirt then consumed directly by postpartum mothers one time a day for seven days. The results obtained are p-value less than 0.05 or 0.001 less than 0.005 with a mean difference in 95% CI of 6.0 (4.0-7.9), thus it can be concluded that postpartum mothers who consume banana stem water at the predetermined dose determined to help accelerate the process of uterine involution compared to postpartum mothers who did not consume banana stem water.  Masyarakat desa Lapan dewa kabupaten Buton Selatan telah terbiasa melakukan etnobutani dengan memanfaatkan air dari tanaman batang pisang atau biasa disebut gedebong pisang bagian bawah sebagai salah satu alternatif dalam pengobatan tradisional yang dikonsumsi selama masa nifas karena diyakini dapat membantu memperlancar proses involusio uteri sehingga meminimalisir terjadinya mencegah perdarahan. Tujuan Penelitian ini yaitu untuk mengetahui normalitas involusio uteri pada ibu nifas yang mengkonsumsi air dari batang pisang. Metode yang digunakan yaitu Quasi Eksperiment, intervensi yang dilakukan yaitu ibu nifas mengkonsumsi air yang telah diambil dari batang pisang ±20-30mldan didiamkan ±10 menit untuk dipisahkan serat atau kotorankemudian dikonsumsi secara langsung oleh ibu nifas sebanyak 1kali dalam sehari selama 7 hari. Hasil yang diperoleh yaitu nilai p kurang dari 0,05 atau 0,001 kurang dari 0,005 dengan perbedaan rerat pada CI95% sebesar 6,0(4,0-7,9), dengan demikian dapat disimpulkan bawah ibu nifas yang mengkonsumsi air batang pisang dengan takaran yang telah ditetapkan dapat membantu mempercepat proses involusio uteri dibandingkan dengan ibu nifas yang tidak mengkonsumsi air batang pisang.